1999
DOI: 10.1016/s0022-5347(01)61692-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of Prediagnostic Selenium Level in Toenails and the Risk of Advanced Prostate Cancer

Abstract: Background:In a recent randomized intervention trial, the risk of prostate cancer for men receiving a daily supplement of 200 µg selenium was one third of that for men receiving placebo. By use of a nested case-control design within a prospective study, i.e., the Health Professionals Follow-Up Study, we investigated the association between risk of prostate cancer and prediagnostic level of selenium in toenails, a measure of long-term selenium intake. Methods: In 1986, 51 529 male health professionals aged 40-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 13 publications
(35 reference statements)
3
64
0
2
Order By: Relevance
“…Studies also examined toenail Se in relation to risk of prostate cancer. The results were inconsistent and inconclusive based on the current evidence [17][18][19][20][21][22][23]. Some studies have related toenail Se to other cancers [24][25][26] In addition, nail specimens were used as biomarkers for other trace elements in cancer studies.…”
Section: Ability Of Nail Trace Element To Predict Chronic Diseasesmentioning
confidence: 99%
“…Studies also examined toenail Se in relation to risk of prostate cancer. The results were inconsistent and inconclusive based on the current evidence [17][18][19][20][21][22][23]. Some studies have related toenail Se to other cancers [24][25][26] In addition, nail specimens were used as biomarkers for other trace elements in cancer studies.…”
Section: Ability Of Nail Trace Element To Predict Chronic Diseasesmentioning
confidence: 99%
“…5 A recent nested case-control study found that the risk of advanced prostate cancer was reduced by one-half to two-thirds for men with the highest selenium status. 11,12 Enthusiasm for selenium in the prevention of prostate cancer comes from Nutrional Prevention of Cancer Study. 4 In this study, 1312 subjects with a prior history of skin cancer were randomized to receive 200 µg/day of selenium in the form of selenized yeast or placebo and had their progress followed for an average of 4.5 years for the development of basal or squamous cell carcinoma of the skin and other cancers.…”
Section: Seleniummentioning
confidence: 99%
“…While most observational studies have shown an inverse association between serum selenium and prostate cancer risk [1][2][3][4][5][6][7][8][9][10], results from two clinical trials are mixed [11,12]. The Nutrition Prevention of Cancer Trial (NPCT) showed a strong protective effect, limited to men with low baseline serum selenium concentrations, while the Selenium and Vitamin E Trial (SELECT), one of the largest cancer prevention trials conducted to date, found no effect of selenium supplementation on prostate cancer.…”
Section: Introductionmentioning
confidence: 99%